Communication In Da’wah In The Digital Age Of Qur'an Perspective - Mukhtarom, Asrori (Tadarus Tarbawy : Jurnal Kajian Islam dan Pendidikan, 2024)
Communication is one of the important elements in da'wah. The success and failure of da'wah is determined by the accuracy of the communication used by da'i as a communicator in conveying messages or information to mad'u whose position as communicant. The purpose of this study is to find out how to proper communication in the da'wah perspective of the Qur'an. This research uses a qualitative descriptive approach with this type of library research. Collect data through the study of books, journals, and literature related to the theme discussed. In understanding the content of the Qur'an using the approach of tafsir maudhu'i / thematic. The results of this study show that the position of communication perspective of the Qur'an occupies a very important position. In the Qur'an the word referring to the meaning of communication is the word al-bayān mentioned in the Qur'an surah ar-Raẖmān[55] verse 4 which means the ability to speak, then the word qaulan which is repeatedly mentioned in the Qur'an among them in surat an-Nisā [3] verse 5 which means speech. The Qur'an gives a hint that in preaching must use proper communication with qaulan ma'rûfan which means speaking in good words or not saying harsh words and hate speech in conveying the message of da'wah. The second uses qaulan sadīdan which means true words or messages conveyed based on facts and do not lie. What the Qur'an hints about communication in da'wah shows that words that contain hate speech and words that contain lies cannot be justified in da'wah activities.